Re‐evaluating the foundations of lncRNA–Polycomb function. (15th March 2017) - Blanco, Mario R; Guttman, Mitchell
Abstract : Many lncRNAs are thought to interact with the polycomb repressive complex 2 (PRC2) in order to regulate gene expression. A central example of this lncRNA–PRC2 paradigm in gene regulation is HOTAIR . In this issue of The EMBO Journal, a study (Portoso et al, 2017 ) reports that while HOTAIR binds PRC2 with high affinity, the complex itself is dispensable for HOTAIR ‐mediated transcriptional silencing. This study raises important questions about the role of PRC2 interactions for lncRNA‐mediated functions and argues for a re‐evaluation of this lncRNA–PRC2 functional paradigm. Abstract : A new study showing Polycomb recruitment to be the consequence—not the cause—of target gene repression by lncRNA HOTAIR questions the role of lncRNA–PRC2 complexes in transcriptional silencing.